Diagnostic accuracy of PSA derivatives for prostate cancer in patients with low prostate-specific antigen levels - Kadeer, Aihemaiti; Maolake, Aerken; Aimaier, Aihemaiti; Abuduwaili, Mukadaisi; Ni, Zecheng; Li, Jiuzhi (Frontiers in Oncology, 2025)
Prostate-specific antigen (PSA) has long been used to screen for prostate cancer (PCa), yet its low diagnostic sensitivity in the so-called PSA “gray zone” often results in overdiagnosis or missed diagnoses. This study aimed to identify reliable diagnostic markers for PCa in patients with serum PSA levels ≤10 ng/mL by comparing various PSA derivatives. Clinical data from 60 patients (PSA ≤10 ng/mL) treated between 2013 and 2023 were retrospectively analyzed. Prostate volume was measured via suprapubic ultrasonography. Receiver operating characteristic (ROC) curves were used to evaluate the diagnostic performance of total PSA (tPSA), free PSA (fPSA), the free-to-total PSA ratio (f/tPSA), PSA density (PSAD), and the PSA-age volume index (PSA-AV). Area under the curve (AUC) values for tPSA, fPSA, f/tPSA, PSAD, and PSA-AV were 0.8301, 0.6830, 0.7225, 0.9318, and 0.9103, respectively. fPSA demonstrated the lowest diagnostic accuracy. tPSA showed moderate performance. Both PSAD and PSA-AV outperformed tPSA and f/tPSA, with positive predictive values of 89.47% and 74.07% and negative predictive values of 87.80% and 93.94%, respectively. PSAD demonstrated higher specificity (94.74%), while PSA-AV showed higher sensitivity (90.91%). PSAD appears to be a superior noninvasive diagnostic marker, while PSA-AV holds promise as an effective screening tool in patients with PSA ≤10 ng/mL. Given the small sample size, these findings should be regarded as preliminary and hypothesis-generating, pending validation in larger multicenter cohorts.